La implementación de la nueva propuesta curricular de la Carrera de Educación Inicial, el caso de la asignatura Educación, Sociedad y Política - Gómez Suikouski, Mayra Alejandra (2018)
This research work addresses the redesign of the Career in Initial Education, which aims to offer a description of the main problems observed in the subject of Education, Society and Politics of students of group one of the race. The purpose is to demonstrate to the teachers responsible for the Initial Education Career the faults and strengths that have been observed, so that they allow the reformulation or restructuring of the activities, methodologies, didactic and technological resources of the chairs that at the beginning were thought. It would be the right way to start this redesign. For this case study, a mixed methodology was used whose purpose was to collect primary data, through the use of techniques such as: interview, survey, direct observation and field diary. The work is organized by chapters; the first one describes the problem where the background, the delimitation and other aspects that allow the understanding of what were the actions that led to the university reformulate and a new curriculum mesh, later is the theoretical framework, the same as supports the data collected with what is proposed in the theory, followed by two chapters, which contains the data collected from the research instruments, the analysis of results and finally the presentation of findings where it is manifested what can be the possible failures or successes so that the new career has a satisfactory course.